2020
DOI: 10.1111/jocs.15074
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of elderly patients receiving continuous flow left ventricular support

Abstract: Background: Heart failure is an epidemic affecting over 6 million people in the United States. Eighty percent of all heart failure patients are older than 65 years of age. Heart transplant is the gold standard treatment for patients suffering advanced heart failure, but only 18.5% of patients receiving heart transplant in the United States are 65 years of age or older. Continuous-flow left ventricular assist devices are a safe and effective therapy for patients with advanced heart failure, and can be used to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Brozzi et al [12 ▪ ] conducted a retrospective study to characterize the long-term outcomes of elderly patients (age >65 years) who received durable LVAD and reported that elderly LVAD recipients had comparable operative outcomes and comparable incidence of major complications, such as gastrointestinal bleeding (24%), drive line infection (13%) and stroke (8%) with younger patients. However, except for patients in INTERMACS profile 1 (Table 1), patients in profiles 2 and 3, had significantly low hospital mortality (50, 10 and 0%, respectively).…”
Section: Left Ventricular Assist Devices In Geriatric Patientsmentioning
confidence: 99%
“…Brozzi et al [12 ▪ ] conducted a retrospective study to characterize the long-term outcomes of elderly patients (age >65 years) who received durable LVAD and reported that elderly LVAD recipients had comparable operative outcomes and comparable incidence of major complications, such as gastrointestinal bleeding (24%), drive line infection (13%) and stroke (8%) with younger patients. However, except for patients in INTERMACS profile 1 (Table 1), patients in profiles 2 and 3, had significantly low hospital mortality (50, 10 and 0%, respectively).…”
Section: Left Ventricular Assist Devices In Geriatric Patientsmentioning
confidence: 99%
“…Data from Brozzi's group 3 and others 9 support the importance of pre‐implant status in determining the hospital mortality of these elderly patients: the less moribund, the better the survival. Therefore, early referral to advanced heart failure and VAD centers is crucial.…”
mentioning
confidence: 95%
“…In this issue of the Journal of Cardiac Surgery, Brozzi et al 3 reviewed long‐term outcomes of 43 elderly patients (age >65 years) who received continuous‐flow (CF) LVADs with 84% received a Heartmate 2 (Abbott Laboratories) and 16%, a Heartware HVAD (Medtronic Inc.) from a single center over a 6‐year period. The average age was 71.5 years, and most patients were in a non‐ambulatory state: 14% were in the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) Profile 1 and 70% Profile 2.…”
mentioning
confidence: 99%
“…To the Editor, The article titled "Long-term outcomes of elderly patients receiving continuous flow left ventricular support" by Brozzi et al 1 was read carefully and attentively due to its high quality and scientific contribution to the medical community. We agree with the authors that the left ventricular assist device (LVAD) should be administered to patients with a low probability of receiving cardiac transplantation.…”
mentioning
confidence: 99%